The Effect Of Governance Mechanisms On Earnings Management With The Moderation Of Financial Distress - Liano, Tristan Jovanka; Ghofar, Abdul (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to examine the effect of corporate governance mechanisms namely institutional ownership, managerial ownership, the proportion of independent board of commissioners, and audit committee size on earnings management with financial distress as a moderating variable. The sample of this study consists of banking companies listed on the Indonesia Stock Exchange during the period 2019–2022 selected using purposive sampling, resulting in 160 observation data points. Using hierarchical multiple linear regression for the analysis, this study finds that institutional ownership and the proportion of independent board of commissioners have a negative effect on earnings management, while managerial ownership and audit committee size have no significant effect on earnings management. Furthermore, financial distress weakens the negative effects of institutional ownership and the proportion of independent board of commissioners on earnings management, but it does not moderate the effects of managerial ownership and audit committee size on earnings management.